1980
DOI: 10.1002/pssa.2210620205
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and thermostimulated luminescence of 0.9 ZrO2–0.1 Y2O3 Single Crystals

Abstract: a) X-ray luminescence spectra of single crystals of composition 0.9 Zr0,-0.1 Y20, and 0.9 Zr0,-0.09 Y20,-0.01 Ln,O, (Ln = Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb) are obtained at room temperature. A wide structureless band of luminescence with a maximum a t about 500nm is found. Thermostimulated luminescence is investigated on the same samples. Irradiation of the crystals by X-rays is carried o u t at room temperature. The glow curves contain two or three peaks each depending on the doping component. The nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 3 publications
3
16
2
Order By: Relevance
“…However, doping itself significantly enhances the formation of a new trapping level responsible for generating the 135°C TL peak. These results resemble an earlier observation of Arsenev et al 9 in which ZrO 2 single crystals doped with oxides of late rare-earth series such as erbium, thallium, and ytterbium can create the new trapping levels in thermoluminescence.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, doping itself significantly enhances the formation of a new trapping level responsible for generating the 135°C TL peak. These results resemble an earlier observation of Arsenev et al 9 in which ZrO 2 single crystals doped with oxides of late rare-earth series such as erbium, thallium, and ytterbium can create the new trapping levels in thermoluminescence.…”
Section: Resultssupporting
confidence: 90%
“…For instance, the natural impurity of Ti in ZrO 2 plays a major role in TL glow, and a previous study adopted the Curie model 7 to aptly describe the trap centers associated with the TL peaks at Ϫ138, Ϫ83, Ϫ73, and 12°C. 8 In a series of studies of TL induced by x ray for 0.9 ZrO 2 Ϫ0.09 Y 2 O 3 Ϫ0.01 Ln 2 O 3 single crystals (Ln ϭdopant), Arsenev et al 9 observed that, although dopants of early lanthanide oxides from Pr until Ho do not produce new trapping levels, dopants of late lanthanide oxides like Er, Tm, and Yb can create a new trapping level with an activation energy of 1.29 eV. In this article, we study the TL glow of 1% Er 2 O 3 -doped ZrO 2 samples irradiated separately with both UV and x-ray radiations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the photoevolution of free electrons from photogenerated F centers in UV-induced colored zirconia (eq 17) and from Zr 3+ in both the original and the UV colored state of zirconia (eq 18) give rise to the 2.5-eV emission band (eq 19) This is in a good agreement with earlier reports, ,, which assigned the emission band at 2.5 eV to F + centers:…”
Section: Resultssupporting
confidence: 90%
“…The principal intrinsic defects in powdered zirconia are anion vacancies, V a . UV irradiation of this dielectric gives rise to broad absorptions in the 250−900-nm spectral region assigned to formation of electron (Zr 3+ , F and F + species) and hole ( V -like) color centers. , Zirconia also exhibits a broad complex emission around 500 nm upon UV excitation at 290 nm and displays X-ray and thermoluminescence in X-ray preirradiated single crystals. Electron trapping by either anion vacancies V a 33,34 or by Ti 4+ impurities in titanium-doped zirconia 35 has been implicated in the mechanism of luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…The emissions observed in PL spectra mostly consist of UV emission, also called near band edge emission (NBE), and visible emission which arise from defects in mediated energy levels. It is now known that the PL spectrum obtained from ZrO 2 [46] translates into emissions from defects known as F (anion vacancies) centers and F + centers as well as from excitons. These defects are mainly controlled by crystalline structure and changes associated with surface morphology [47][48][49].…”
Section: Photoluminescence (Pl) Studiesmentioning
confidence: 99%